Design Of Digital Smart Board As A New Information Media With Arduino Control - Hardian Saputra; Solly Aryza; Siti Anisah (INFOKUM, 2021)
The development of information media at this time many Changes are increasingly rapid in the field of information and digital technology, where at this time everyone can see how examples of digital technology that are around us such as information tools or announcements in digital form, for example, such as a Smart Board which is a tool that functions to display information, advertisements, warnings and others that are formal or informal. Therefore, digital smart boards are needed in this developing era where this research has a specific purpose and gives an attractive impression when viewed by the public. Arduino Uno microcontroller as the controller. Where all information and displays are presented in the LED Dot Matrix and controlled by Android and then transferred via Bluetooth from a certain distance. From the results of this design analysis, it can be concluded that in the microcontroller, Arduino Uno and controlled by Android via Bluetooth, various kinds of word characters a welcome display that can be controlled by android via data transfer using via bluetooth and displays word characters in the Led Dot Matrix.